The crystal chemistry and hydrogen storage properties of light metal borohydrides - Culligan, SD (2013)
This work examines various light metal borohydrides, particularly those formed from group II metals, with the aim of understanding their fundamental physical properties and improving their hydrogen storage ability. The structure of a new phase (γ) of Mg(BH4)2 is reported and the decomposition is fully characterized in a combination of diffraction and thermogravimetric studies. The bulk properties of γ-Mg(BH4)2 are compared to those of an SiO2 isostructure and probed by various neutron scattering techniques. Negative thermal expansion is observed at low temperatures and the material absorbs up to 1.5 moles of hydrogen gas to form one of the most gravimetrically hydrogen-dense materials ever reported. The structural evolution of Ca(BH4)2 under different synthetic conditions and external influences (e.g. temperature) is studied up until the material decomposes. The effects of various additives on group II metal borohydrides are also examined and the influence of each is justified by observing subtle structural changes in the mixed system via in situ synchrotron X-ray powder diffraction and 11B NMR measurements.